Turmeric extract reverses diclofenac-induced malondialdehyde elevation: comparative efficacy of two therapeutic doses - Kevin Sunyoto; Anita Lidesna Shinta Amat; Rr Listyawati Nurina; Kartini Linda (Indonesian Society for Biochemistry and Molecular Biology, 2026)
Background: Chronic administration of non-steroidal anti-inflammatory drugs (NSAIDs) such as diclofenac sodium generates excessive reactive oxygen species (ROS), causing lipid peroxidation and elevated malondialdehyde (MDA) levels, a biomarker of oxidative tissue damage. Turmeric extract (Curcuma longa L.) contains curcuminoids with antioxidant properties that may reduce MDA formation and mitigate NSAID-induced injury. Objectives: To determine the effect of turmeric extract on malondialdehyde (MDA) levels in white rats (Rattus norvegicus) induced with sodium diclofenac. Methods: This laboratory experimental study employed a posttest-only control group design. Twenty-eight white rats were divided into four groups: normal control, negative control (diclofenac 10 mg/kg), treatment 1 (diclofenac + extract 100 mg/kg), and treatment 2 (diclofenac + extract 200 mg/kg). MDA levels were measured spectrophotometrically. Data were analyzed using One-Way ANOVA and post hoc Dunnett T3 test. Results: Turmeric extract significantly reduced MDA levels (p<0.001). The 200 mg/kg dose demonstrated superior protective effects compared to 100 mg/kg, effectively preventing diclofenac-induced oxidative stress. Conclusion: Turmeric extract demonstrates dose-dependent protective effects against diclofenac-induced oxidative stress, with 200 mg/kg achieving 18.3% MDA reduction and restoring oxidative balance. These findings support its potential as adjunct therapy for chronic NSAID users.